Antibacterial activities of Carica papaya L. seed as food preservative - Abdullah Sani, Muhamad Shirwan (2018)
Presently, no known commercial application of Carica papaya seeds has been recorded. It is mainly discarded; therefore, the aim of this study is to evaluate the potential of these seeds as a source of antibacterial compounds for possible application as food preservatives. The phytochemical components and extraction efficiency were first carried out using ten different solvents based on different polarities. The best solvent extraction was further carried out and improved by evaluating the effect of sonication (SAE), contact time (CT) and solvent-to-solid ratio (SSR). The effective of the initial extraction and the improved method were evaluated by determining the total phenolic and flavonoid contents and antibacterial activity against Salmonella enteritidis, Bacillus cereus, Vibrio vulnificus and Proteus mirabilis as indicator microorganisms. The composition of the Carica papaya seed crude extract, hexane: ethyl acetate (1:1) fraction and sub-fraction C were identified using gas chromatography mass spectrometer (GC/MS). The antibacterial activity and toxicity of these extracts were also studied. The most potent with least toxic extract was evaluated for antibacterial activity and stability as antibacterial agent in food model systems and finally as an antibacterial agent in yellow noodle. Based on disk diffusion (DDT) and minimum inhibitory concentration (MIC) tests, the hierarchy of extract potency can be ranked as methanol > acetone > acetonitrile > chloroform > hexane > diethyl ether = petroleum ether > ethanol > dichloromethane. The S. enteritidis, V. vulnificus, P. mirabilis and B. cereus were selected as indicator microorganisms in this study due to the lowest MIC (5.63 mg/mL). Improved extraction of Carica papaya seed antibacterial compounds was best performed without SAE at 8 h CT with 10:1 SSR. These SAE, CT and SSR extraction treatments produced the yield of 21.59 - 81.15 mg/g, 20.10 - 62.78 mg GAE/g DW of TPCs, the lowest MIC (5.63 mg/mL), MIC50 (1.87 - 3.67 mg/mL) and the lowest MIC0 (< 0.02 mg/mL). The antibacterial activity of crude and partially purified Carica papaya seed extracted on S. enteritidis, V. vulnificus, B. cereus and P. mirabilis were evaluated using bioautography of thin layer chromatography (TLC) and MIC test which had found that hexane: ethyl acetate (1:1) fraction and sub-fraction C (Rf = 0.94 ± 0.03) showed highest bioautographic potency against tested microorganisms; however, having equal MIC (5.63 mg/mL) but higher toxicity (LC50 = 1.797 mg/mL and 0.332 mg/mL, respectively) as compared to crude extract (LC50 = 5.505 mg/mL). Thus, indicating the latter was adopted for further antibacterial application study. Twenty-one groups of components were identified in derivatized and non-derivatized crude extracts using GC/MS where fatty acids and fatty acid methyl esters (80.23%) were the major components. Cisvaccenic acid, which was the dominant component in sub-fraction C, in pure form had demonstrated the lowest MIC against B. cereus (1.41 mg/mL), P. mirabilis (1.41 mg/mL) and S. enteritidis (0.70 mg/mL); thus, signifying its potency as antibacterial component in the extract. The extract had shown potency in acidic condition (pH 4), water activity > 0.909 and temperature < 80°C at 5.63 mg/mL (MIC). The extract was capable of inhibiting the tested microorganisms in 5%, 10%, 20% and 30% of carbohydrate and 2%, 5%, 10% and 15% oil media and 5% protein medium. The shelf life of yellow noodle treated with Carica papaya seed extract was extended from 3 d - 12 d for 1.41, 5.63, 11.25 and 22.5 mg/g extracts and from 3 d - 10 d for 0.70 mg/g extract. The principle component (PCA), cluster (CA) and discriminant (DA) analyses had indicated the effective time of antibacterial activity of Carica papaya seed and the safe consumption of the treated yellow noodle was to be at least by day sixth of storage. In conclusion, Carica papaya seed extract is a potential antibacterial extract that able to act as a food preservative.